Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2966.2010.18113.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hubble Space Telescope GOODS NICMOS Survey: overview and the evolution of massive galaxies at 1.5< z< 3

Abstract: We present the details and early results from a deep near-infrared survey utilizing the NICMOS instrument on the Hubble Space Telescope centred around massive M * > 10 11 M galaxies at 1.7 < z < 2.9 found within the Great Observatories Origins Deep Survey (GOODS) fields North and South. The GOODS NICMOS Survey (GNS) was designed to obtain deep F160W (H-band) imaging of 80 of these massive galaxies and other colour-selected objects such as Lyman-break dropouts, BzK objects, distant red galaxies (DRGs), extremel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 80 publications
4
76
0
Order By: Relevance
“…These massive galaxies are in the redshift range z = 1.7-2.9 and at a depth of three orbits. The galaxies are redshift selected based on their optical to infrared colour described in Conselice et al (2011). Details on the data reduction pipeline are described in Magee, Bouwens & Illingworth (2007).…”
Section: The Goods Nicmos Surveymentioning
confidence: 99%
“…These massive galaxies are in the redshift range z = 1.7-2.9 and at a depth of three orbits. The galaxies are redshift selected based on their optical to infrared colour described in Conselice et al (2011). Details on the data reduction pipeline are described in Magee, Bouwens & Illingworth (2007).…”
Section: The Goods Nicmos Surveymentioning
confidence: 99%
“…The epoch between z ∼ 3 and z ∼ 1 appears to be crucial for the assembly of massive galaxies, as many authors find that the number density of galaxies with masses around 10 11 M and larger evolves very rapidly over this period of time (Fontana et al 2006;Marchesini et al 2009;Ilbert et al 2010;Conselice et al 2011). By redshift z ∼ 1, however, the number density of early-types is comparable to the local one, with an increase of a factor of 1.5 allowed at most (Cimatti et al 2006;Franceschini et al 2006;Borch et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Observational data have shown that galaxies in the local universe generally fall into two categories: quiescent ellipticals, which dominate the massive galaxy population (M * 10 10.5 M ), and blue star-forming disk galaxies, which occupy the lower mass regime Balogh et al 2004;Kauffmann et al 2003). This color bimodality, which groups galaxies into the "blue cloud" and "red sequence," exists not only in the local universe, but also out to redshift z ∼ 1 (Bell et al 2004;Willmer et al 2006), and possibly up to z = 2 and beyond (Pozzetti et al 2010;Conselice et al 2011). The origin and the evolution of this color bimodality are largely unknown.…”
Section: Introductionmentioning
confidence: 99%